If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(-6+x)=4
We move all terms to the left:
-2(-6+x)-(4)=0
We add all the numbers together, and all the variables
-2(x-6)-4=0
We multiply parentheses
-2x+12-4=0
We add all the numbers together, and all the variables
-2x+8=0
We move all terms containing x to the left, all other terms to the right
-2x=-8
x=-8/-2
x=+4
| 4r+3=-5 | | -86+4x=117+11x | | -3x+4=2x-11 | | x+7=3(5+2x) | | 6e+8=5e+17 | | 6-2x-4x=21 | | 2g2−3g−3=0 | | 3+6x=4x+9* | | -2-3r=-8-4r | | 8t=(-32) | | -6-2=5t+8 | | -3x-125=7x+115 | | -6y+-1=5 | | 6x-173=124-5x | | w/2-10=6 | | 5(1+x)=x-3 | | 4(5x-5)=180 | | 2x+15+8x=15 | | 49=144x^2 | | 9a-9=9 | | x/5+26=37 | | k-3/10=-2/5 | | -174+2x=90-10x | | 31=w/4+17 | | h+3=1 | | -62+6x=70+10x | | 2(d+1)-3=3 | | 5(1+x)=5x | | -z-4=-10+z | | 7.5x-(2.25x+15)=0 | | 5+-4n=-15 | | -2(x-15)=-5 |